2018
DOI: 10.1080/23294515.2018.1462273
|View full text |Cite
|
Sign up to set email alerts
|

How acceptable is paternalism? A survey-based study of clinician and nonclinician opinions on paternalistic decision making

Abstract: We conducted an empirical study to explore clinician and lay opinions on the acceptability of physician paternalism. Respondents read a vignette describing a patient with brain hemorrhage facing urgent surgery that would be lifesaving but would result in long-term severe disability. Cases were randomized to show either low or high surrogate distress and certain or uncertain prognosis, with respondents rating the acceptability of not offering brain surgery. Clinicians (N = 169) were more likely than nonclinicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Given these considerations, clinicians should approach the decision-making process collaboratively, negotiating the role of the clinician with surrogates ( 98 ) rather than taking a default paternalistic approach ( 99 ). Though few providers enquire about the surrogate's preferred role in decision-making ( 98 ), providers should ascertain a decision-maker's preferred level of control over EOL care decisions.…”
Section: Shared Decision-making With Surrogates: Ideal Processesmentioning
confidence: 99%
“…Given these considerations, clinicians should approach the decision-making process collaboratively, negotiating the role of the clinician with surrogates ( 98 ) rather than taking a default paternalistic approach ( 99 ). Though few providers enquire about the surrogate's preferred role in decision-making ( 98 ), providers should ascertain a decision-maker's preferred level of control over EOL care decisions.…”
Section: Shared Decision-making With Surrogates: Ideal Processesmentioning
confidence: 99%
“…However, one recent study found that paternalistic decision‐making (and prioritising technical expertise) when clinicians, patients and their families disagree had far less support among the lay public than among clinicians, highlighting how ideas of ethical decision‐making may differ between clinicians and those they treat (Bailoor et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Such unilateral decision making, however benevolent its justification, is now widely considered anathema in the context of patient care, despite occasional calls for more nuanced consideration of the potential role and value of particular forms of paternalism in some contexts. [8][9][10] Respect for autonomy and, specifically, the ethical and legal requirement to obtain valid consent for treatment or participation in research, is considered a vital protection for patients.…”
Section: The Evolution Of Patient Autonomy In Bioethicsmentioning
confidence: 99%